2016
DOI: 10.17344/acsi.2016.2484
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Activity Signature of Key Carbohydrate Metabolism Enzymes in Phenolic-rich Grapevine Tissues

Abstract: Physiological studies in plants often require enzyme extraction from tissues containing high concentrations of phenols and polyphenols. Unless removed or neutralized, such compounds may hinder extraction, inactivate enzymes, and interfere with enzyme detection. The following protocol for activity assays for enzymes of primary carbohydrate metabolism, while based on our recently published one for quantitative measurement of activities using coupled spectrophotometric assays in a 96-well format, is tailored to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…Recent studies on BN have shown several transcriptional and metabolic changes in the host plant. Specifically, the genes involved in primary and secondary metabolism are changed in response to infection; several photosynthetic genes are largely down-regulated in infected plant tissues, whereas the genes involved in carbohydrate metabolism, genes associated with the flavonoid synthesis pathway, some genes encoding pathogenesis-related (PR) proteins and genes associated with reactive oxygen species production are significantly induced (Hren et al 2009a, b;Albertazzi et al 2009;Landi and Romanazzi 2011;Santi et al 2013;Covington Dunn et al 2016). Several metabolites associated with activities of the enzyme products of these genes have also been demonstrated as increased in infected plants (Prezelj et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on BN have shown several transcriptional and metabolic changes in the host plant. Specifically, the genes involved in primary and secondary metabolism are changed in response to infection; several photosynthetic genes are largely down-regulated in infected plant tissues, whereas the genes involved in carbohydrate metabolism, genes associated with the flavonoid synthesis pathway, some genes encoding pathogenesis-related (PR) proteins and genes associated with reactive oxygen species production are significantly induced (Hren et al 2009a, b;Albertazzi et al 2009;Landi and Romanazzi 2011;Santi et al 2013;Covington Dunn et al 2016). Several metabolites associated with activities of the enzyme products of these genes have also been demonstrated as increased in infected plants (Prezelj et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The protocol established in this study to determine an antioxidant activity signature complements the previously established protocols for enzymatic profiling of carbohydrate metabolism [23,[42][43][44]51] that proved to be very useful in various studies [45][46][47]. Notably, the extraction protocol described in this study for the nine antioxidant activities is compatible with the experimental platform described earlier by us to determine 13 key enzymes of carbohydrate metabolism [23], that had been extended to a fructan active enzyme [51].…”
Section: Discussionmentioning
confidence: 84%
“…The established analytical platform to analyze the activities by a semi-high throughput technique will complement the analyses of mRNA levels by qPCR or truly high-throughput techniques. Thus, it will be possible to overcome the limitation of often poor correlation between transcript levels and the enzymatic activity in the tissue that ultimately determines the phenotype [53]. Furthermore, it will be possible to assess the possible involvement of epigenetic, posttranscriptional and posttranslational mechanisms [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have analyzed the expression of genes involved in carbohydrate metabolism and their enzyme products and sugar metabolites upon infection of grapevines with 'Ca. P. solani' [8,[16][17][18][19][20]. As a sign of stress conditions, grapevines infected with 'Ca.…”
Section: Introductionmentioning
confidence: 99%